Evidence of microbial activity in siderite and calcite deposits on gastropod shells in Pliocene sand and clay beds from Lipovljani, Croatia - Posilović, Hrvoje (Array, 2008)
Summary: Freshwater Pliocene sand and clays found near Lipovljani in western Slavonia, Croatia, contain gastropods preserved by diagenetic mineral incrustations of alternating calcite and siderite. The geochemical possibility of siderite formation is evaluated, and evidence for microbial mediation of siderite deposition around fossil carbonate shells is presented